FATTYA ACID COMPOSITION AND FLAVOUR PROFILE ANALYSIS OF CARDAMOM ESSENTIAL OIL - M.D .SONTAKKE; R.V. KALE; V.R. CHAVAN; G.S. RAUT (The Bioscan, 2019)
Spices are food ingredients, popular in every cuisine they can be used in food products, due to their flavoring properties, taste, aroma, and color. In the present investigation the essential oil was extracted from cardamom by hydro-distillation using clevenger apparatus. The extracted essential oil were assessed for various physical and chemical characteristics. Results revealed that cardamom essential oil iodine value was found to be 90.56 (g/ 100g), acid value (8.7 mg KOH/g) and had lower peroxide value (7.5 g/kg). Fatty acid composition of cardamom essential oil were identified more than 40 compounds which represents 98.5 percent of all the compounds detected. The major compounds detected were á-Terpinyl acetate (37.55 percent), 1,8-Cineole (32.83 percent), Linalyl acetate (5.42 percent), Sabinene (4.99 percent), Linalool (4.44 percent), Myrcene (2.12), Limonene and á- Terpineol (1.88 percent) were investigated. Further, cardamom essential oil was also studied for fatty acid composition. It could be concluded that 1,8-cineole and á-Terpinyl acetate are the major component of cardamom essential oil known for its pleasant spicy aroma and taste. The cardamom essential oil can be used as a flavouring compound in formulation of food products.